Integrated Design of a Secondary School - salameh, ASSil; abu shokor, Hamed; abeed, Mo’ath (My University, 2017)
This project represents a design of a school in an integrated, effective and modern way. This design gave it the benefit to be more environmental, comfortable for student to learn effectively. Besides that, a building information modelling (BIM) process was done in the project, this process represents a digital modelling of every component in the building, which will allow the design to be more effective. To achieve this design, a set of aspects should be covered which are Architectural aspect, structural aspect, in addition to environmental aspect. The main objective of this project is to provide an environmental and convenient design that meets the needs of the students. In terms of methodology, this research was implemented within three stages The first stage is doing a literature review, which represented in collecting the essential theoretical information about school design such as standard areas of spaces, best orientation of building and spaces. The second stage is field work (site analysis stage) and include measurement of areas of the site, measurement of sound and noise around the site, daylight. The last stage is case study analysis which helped in knowing the problems that may happen and how to solve these problems and choosing the best solution for these problems. In Palestine, there are a specific number of projects that is approximately similar to our project, but our project is different because of the idea of designing more spaces that serve different activities, as well as providing the BIM system.